Sports metaresearch: An emerging discipline of sport science and medicine - Warmenhoven, J.; Menaspà, P.; Borg, D. N.; Vazire, S.; White, N.; Sainani, K.; Nimphius, S.; Coutts, A. J.; Impellizzeri, F. M. (Sports Medicine, 2025)
Inadequacies in the conduct and quality of research are well established across many research domains, including sport science and medicine. Metaresearch - the practice of performing research on research - is presented as a practical vehicle for improving research quality through evaluating the research processes. This article introduces the concept of metaresearch to sport as a new sub-field of sport science. The broad types of metaresearch are introduced, with a mapping of current sports metaresearch activity across these areas. Interdisciplinary centres aimed at improving scientific quality across other fields are also introduced to sport, and specific considerations for beginning metaresearch are provided for sport. This includes, for example, not performing metaresearch poorly, beginning evaluative metaresearch early to intervene before bad practice becomes normalised, leveraging required interdisciplinary expertise depending on the metaresearch question and undertaking an ethical approach for carrying out evaluation of research quality.